Evaluation of Cytomegalovirus Seroprevalence in Pregnant Women: A Multicenter Study - Merve Sefa Sayar; Yasemin Çağ; Neziha Yılmaz; Seniha Şenbayrak; Tuba Damar Çakırca; Özge Çaydaşı; Deniz Gür Altunay; Esra Erdem Kıvrak; Deniz Özer; Esma Eryılmaz Eren; Fisun Vural; Sevil Alkan; et al. (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Cytomegalovirus (CMV) infection during pregnancy poses a significant risk of congenital infection, particularly in seronegative women. This study aimed to assess CMV seroprevalence among pregnant women and evaluate the incidence of primary CMV infections during pregnancy. Materials and Methods: This retrospective multicenter study included pregnant women aged ≥18 year who were hospitalized between January 2018 and December 2022. Demographic data - including maternal age, gravidity, and educational and occupational status - along with CMV serological results, gestational age at CMV diagnosis, and fetal ultrasonographic (USG) findings were collected and analyzed. In cases with positive CMV immunoglobulin M (IgM) and IgG, CMV-IgG avidity values, amniotic fluid CMV-DNA polymerase chain reaction results, and fetal USG findings were recorded to assess the likelihood of primary infection. Results: Among 16,761 pregnant women, 261 (1.6%) tested positive for CMV-IgM. Of these, 126 (48.3%) underwent CMV-IgG avidity testing, and three cases demonstrated low avidity, indicating recent primary infection. Ultrasonographic abnormalities in these three fetuses included hydrops fetalis, polyhydramnios, skin edema, and hyperechogenic bowel. Despite high CMV-IgG avidity, five cases showed abnormal findings on detailed fetal ultrasonography namely intrauterine growth restriction, oligohydramnios, and cranial anomalies. Conclusion: Primary CMV infection during pregnancy is associated with adverse outcomes such as fetal anomalies, spontaneous abortion, and preterm birth. Preventive strategies, including educating CMV-seronegative women about transmission routes and routine assessment of CMV-IgG avidity and fetal USG findings, are essential for early diagnosis and improved perinatal outcomes.